2019
DOI: 10.3390/biomimetics4040077
|View full text |Cite
|
Sign up to set email alerts
|

On the Fluid Dynamical Effects of Synchronization in Side-by-Side Swimmers

Abstract: In-phase and anti-phase synchronization of neighboring swimmers is examined experimentally using two self-propelled independent flexible foils swimming side-by-side in a water tank. The foils are actuated by pitching oscillations at one extremity—the head of the swimmers—and the flow engendered by their undulations is analyzed using two-dimensional particle image velocimetry in their frontal symmetry plane. Following recent observations on the behavior of real fish, we focus on the comparison between in-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Our experiments demonstrate that, for biomimetic robots, swimming in pairs results in an increase in speed and efficiency, and a decrease in power consumption, when compared with swimming alone (figure 6). While this is similar to the results acquired from earlier studies [13,15,17,18,44], we additionally find that two fish swimming out-of-phase will probably benefit from a higher swimming efficiency, which was not previously observed [15,18] (figure 6). This novel finding is likely to be the result of the nominally realistic physical model we employ that accounts for the effects of three-dimensional body shape [45], self-propelled system [29] or flexible caudal fin [46].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our experiments demonstrate that, for biomimetic robots, swimming in pairs results in an increase in speed and efficiency, and a decrease in power consumption, when compared with swimming alone (figure 6). While this is similar to the results acquired from earlier studies [13,15,17,18,44], we additionally find that two fish swimming out-of-phase will probably benefit from a higher swimming efficiency, which was not previously observed [15,18] (figure 6). This novel finding is likely to be the result of the nominally realistic physical model we employ that accounts for the effects of three-dimensional body shape [45], self-propelled system [29] or flexible caudal fin [46].…”
Section: Discussionsupporting
confidence: 92%
“…Fish likely swim together to reap many benefits of congregation, which include reduced predation risk [4], increased foraging efficiency [5] and improved environmental sensing capabilities [6]. It has also been hypothesized that, from a biophysical standpoint, swimming in schools may benefit individuals energetically, since it could allow them to extract power from the vortices shed by their neighbours [7][8][9][10][11][12][13][14][15][16]. However, by virtue of swimming in close proximity to a conspecific, the resulting fluid mechanic interactions between the adjacent fish are likely to result in a different flow structure from that in solitary swimming [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashraf et al, by contrast, suggested that a simple "phalanx" formation (swimming in a line) may provide a significant energetical benefit (Ashraf et al, 2017). The choice of relative phase is associated with the relative position between fish: preference of synchronization between nearby fish (in-phase or anti-phase) is observed in fish swimming experiments (Ashraf et al, 2016(Ashraf et al, , 2017, while the beneficial outcome of synchronization are confirmed numerically (Li et al, 2019a) and experimentally (Godoy-Diana et al, 2019). Besides synchronization, recent studies also suggest that matching the vortex phase of a neighboring fish is an effective means to improve the energetic efficiency (Daghooghi and Borazjani, 2015;Khalid et al, 2016;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These highly three-dimensional spatial configurations found within collectives can be decomposed into canonical in-line, side-by-side, or tip-to-tip arrangements as presented in Figure 1 . To date, these interactions have mostly been studied for propulsors in in-line arrangements [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], although a few efforts have been made to understand interactions in side-by-side arrangements [ 20 , 21 , 22 , 23 ], as well as staggered arrangements [ 24 , 25 , 26 , 27 ]. Here, our focus is on the propulsive performance and flow interactions in in-line , and staggered arrangements.…”
Section: Introductionmentioning
confidence: 99%